Gasto público, tributos e desigualdade de renda no Brasil - Marcelo Medeiros; Pedro Souza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Using a factor decomposition of the Gini coefficient we measure the contribution to inequality of direct monetary transfers to and from the Brazilian State. Among the transfers from the State are wages of public workers, pensions and social assistance; the transfers to the State are direct taxes. Data comes from the Brazilian POF 2008-2009. The results indicate that the State contributes directly and to a large share of inequality. Factors associated to work in the public sector - wages and pensions - are very concentrated and regressive. Factors related to the private sector are still concentrated, but progressive. Redistributive mechanisms that could revert this inequality, such as taxes and social assistance, are very progressive but proportionally small; consequently their effect is completely offset by the regressive transfers from the State. Contrary to what has been found in other countries, public spending with work and social policies is concentrated in a small oligarchy and, taken as a whole, tends to increase inequality.
Keywords: D31; D33; D63; H22; H23; H53; H55; I38; J45; 330; income distribution; social inequality; welfare state; social policies; public work; pensions